Preparation method of magnetic graphene capable of being oriented in magnetic field
Through the magnetic graphene coating oriented under magnetic fields, the problem of structural damage of cement-based materials in harsh environments is solved, more efficient protection effect is achieved, and the service life of concrete is extended.
Patent Information
- Application Number
- CN202411201907.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-02-18
AI Technical Summary
Cement-based materials are prone to structural damage in strict marine environments, and existing coatings are difficult to effectively protect in such environments, resulting in high maintenance costs.
Using a magnetic graphene preparation method that can be oriented in a magnetic field, by coating magnetic nanoparticles with silica and mixing them with graphene powder, the graphene layer by layer is oriented by using the magnetic field generated by the conductive coil to form a uniform coating. layer.
Through the orientation of graphene, a dense protective layer is formed, which improves the crack resistance and thermal shock cracking resistance of cement-based materials, and enhances the protection of steel bars and extends the service life of concrete.
Smart Images

Figure CN119463541A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building surface coatings, and in particular to a method for preparing magnetic graphene that can be oriented in a magnetic field. Background Art
[0002] Cement-based materials play an extremely important role in national infrastructure and major projects. However, in some special use environments, such as marine environments, cement-based materials are subjected to harsh use environments, causing damage to concrete structures. The annual maintenance cost of cement-based materials worldwide exceeds one trillion yuan. It is difficult to provide good protection in harsh environments using only daily-use coatings. Since its discovery, graphene has demonstrated extremely excellent physical and chemical properties. Combining it with coatings and orienting it along the plane direction can form a dense barrier structure on the surface of the concrete matrix, increase the tortuosity of ion migration, improve the crack resistance of cement-based materials, enhance the material's resistance to thermal shock cracking, and protect the steel bars, which is of great significance for improving the service life of concrete. Summary of the invention
[0003] In view of this, the present invention aims to provide a graphene that can be oriented in a magnetic field.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0005] 1. A method for preparing magnetic graphene that can be oriented in a magnetic field, characterized in that it comprises the following steps:
[0006] 1) Preparation of silica-coated magnetic particles: magnetic nanoparticles are stirred and mixed with an aqueous solution of ethanol, and then tetraethyl orthosilicate is added and stirred continuously, and then ammonia water is added and stirred continuously;
[0007] 2) Preparation of phenyl-modified silica-coated magnetic particles: first add ammonia water, then add siloxane and continue stirring, then filter and wash until the pH of the washing solution is 7;
[0008] 3) Preparation of magnetic graphene: The prepared phenyl-modified silica-coated magnetic particles are dispersed in ethanol, and then graphene powder is added and stirred at a certain temperature, so that the two are assembled together through the π-π stacking effect of the non-covalent bond between the phenyl groups in the phenyl-modified silica-coated magnetic particles and the graphene benzene rings;
[0009] 4) Orientation of magnetic graphene in a magnetic field: The magnetic graphene ethanol dispersion is applied to the surface coating of a building. During construction, the prepared magnetic graphene ethanol dispersion is first sprayed on the surface of the object to be constructed, and then an energized conductive coil is used to scan the surface of the coating to be constructed. The magnetic field generated by the conductive coil causes the magnetic graphene to be stacked and oriented layer by layer to form a uniform coating.
[0010] 2. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that the magnetic nanoparticles in step 1) are nano iron powder, nano ferroferric oxide powder, nano nickel powder, nano steel powder, and have a particle size of 1-500 nm.
[0011] 3. The method for preparing magnetic graphene oriented in a magnetic field according to claim 1, wherein the volume ratio of the alcohol water in the ethanol aqueous solution in step 1) is 2-10, the volume ratio of ethanol to tetraethyl orthosilicate is 5-20, and the volume ratio of ethanol to ammoniacal liquor is 1-2.5.
[0012] 4. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, wherein the dropping speed of tetraethyl orthosilicate in step 1) is 0.5-20 mL / min.
[0013] 5. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that, in step 1), the stirring speed is 500-5000 rpm, the stirring mixing time of the magnetic nanoparticles and the ethanol aqueous solution is 10-60 min, the stirring time after adding tetraethyl orthosilicate is 10-60 min, and the stirring time after adding ammonia water is 0.5-4 h.
[0014] 6. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that the siloxane in step 2) is one or more of phenyltrimethylsiloxane, methylphenylsiloxane, and dimethyldiphenylsiloxane.
[0015] 7. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that the volume ratio of the ammonia water added in step 2) to the ammonia water in step 1) is 0.25-0.8, and the volume ratio of the siloxane in step 2) to the tetraethyl orthosilicate in step 1) is 0.05-0.4.
[0016] 8. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that the dropping speed of siloxane in step 2) is 0.1-15 mL / min.
[0017] 9. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that the stirring speed in step 2) is 500-5000 rpm and the stirring time is 0.5-5h.
[0018] 10. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that the concentration of the ethanol dispersion of the phenyl-modified silica-coated magnetic particles in step 3) is 2-20 g / L, and the mass ratio of graphene powder to phenyl-modified silica-coated magnetic particles is 0.5-20.
[0019] 11. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that the stirring rate in step 3) is 100-500 rpm, the stirring temperature is 30-70°C, and the stirring time is 10-24h.
[0020] 12. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that the number of turns of the coil in step 4) is 50-500 turns, and the current is 0.1-5A.
[0021] Compared with the prior art, the induction heat-induced gelling material of the present invention has the following advantages:
[0022] 1. After the graphene coating is sprayed, the conductive coil scans back and forth on the coating surface, so that the conductive coil generates an electromagnetic field that acts vertically on the coating surface to orient the graphene. The operation is relatively convenient, and the intensity of the electromagnetic field can be adjusted according to the type, concentration and thickness of the coating to achieve the best orientation effect of graphene.
[0023] 2. Compared with randomly oriented graphene, oriented graphene can form a dense graphene protective layer on the surface of concrete, thereby improving the protective effect of graphene.
[0024] 3. In the horizontal space parallel to the substrate plane, it can enhance the wear resistance of the concrete surface, improve the thermal shock cracking resistance of the surface material, and can be combined with electronic equipment to detect the service status of the concrete.
[0025] 4. In the longitudinal space perpendicular to the plane of the substrate, it can prevent the migration of insulators, improve the seismic performance of the material, and improve the thermal insulation performance of the protective layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0027] Figure 1 is a schematic diagram of graphene of the present invention, wherein Figure 1 (a) is the original graphene, Figure 1 (b) is the modified magnetic graphene. Explanation of reference numerals: 1-graphene sheet, 2-phenyl-modified silica-coated magnetic particles.
[0028] Figure 2 The graphene coating is randomly distributed on the concrete substrate of the comparative example of the present invention. Explanation of the reference numerals: 1-coating, 2-original graphene, 3-concrete substrate.
[0029] Figure 3 This is a graphene coating oriented and distributed on a concrete substrate under the action of an electromagnetic field according to an embodiment of the present invention. Explanation of reference numerals: 1-magnetic flux lines, 2-coil movement direction, 3-coil (blue arrow is current direction), 4-coating, 5-magnetic graphene, 6-concrete substrate. DETAILED DESCRIPTION
[0030] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0031] The present invention will be described in detail below with reference to the accompanying drawings and embodiments.
[0032] Embodiment 1:
[0033] 1) Preparation of silica-coated magnetic particles: Nano nickel powder with a particle size of 10 nm and an ethanol aqueous solution were stirred and mixed at a speed of 1000 rpm for 30 min, tetraethyl orthosilicate was added at a drop rate of 1 mL / min and continued to be stirred for 20 min, and then ammonia water was added and continued to be stirred for 2 h, wherein the volume ratio of ethanol to water in the ethanol aqueous solution was 8, the volume ratio of ethanol to tetraethyl orthosilicate was 10, and the volume ratio of ethanol to ammonia water was 1;
[0034] 2) continuing to add ammonia water, and then adding phenyl trimethylsiloxane at 0.5 mL / min, and continuing to stir at a speed of 500 rpm for 4 hours, and then filtering and washing until the pH of the washing liquid is 7, wherein the volume ratio of the ammonia water added in step 2) to the ammonia water in step 1) is 0.4, and the volume ratio of the siloxane in step 2) to the tetraethyl orthosilicate in step 1) is 0.1;
[0035] 3) dispersing the prepared phenyl-modified silica-coated magnetic particles in ethanol to prepare a 10 g / mL ethanol dispersion of phenyl-modified silica-coated magnetic particles, adding graphene powder, stirring at 40° C. and 200 rpm for 12 h, and assembling the two together through the π-π stacking effect of the non-covalent bond between the phenyl groups in the phenyl-modified silica-coated magnetic particles and the graphene benzene rings, wherein the mass ratio of the graphene powder to the phenyl-modified silica-coated magnetic particles is 10;
[0036] 4) The magnetic graphene ethanol dispersion is dispersed in the paint and applied to the surface coating of the building. During construction, the prepared magnetic graphene paint is first sprayed on the surface of the object to be constructed, and then an energized conductive coil is used to scan the surface of the constructed coating. The magnetic field generated by the conductive coil causes the magnetic graphene to be stacked and oriented layer by layer to form a uniform coating.
[0037] 5) After the coating is completely dry, scrape off the formed graphene coating and perform a Raman spectrum test to test the intensity ratio of the D peak to the G peak.
[0038] In this embodiment, the intensity ratio of the D peak to the G peak is 0.42.
[0039] Embodiment 2:
[0040] 1) Preparation of silica-coated magnetic particles: Nano iron powder with a particle size of 20 nm and an ethanol aqueous solution were stirred and mixed at a speed of 1500 rpm for 20 min, tetraethyl orthosilicate was added at a drop rate of 5 mL / min and continued to stir for 30 min, and then ammonia water was added and continued to stir for 3 h, the volume ratio of ethanol to water in the ethanol aqueous solution was 5, the volume ratio of ethanol to tetraethyl orthosilicate was 15, and the volume ratio of ethanol to ammonia water was 2;
[0041] 2) continue to add ammonia water, and then add a mixed solution of methylphenylsiloxane and phenyltrimethylsiloxane at a volume ratio of 4:1 at 1 mL / min, continue stirring at a speed of 700 rpm for 3 hours, and then filter and wash until the pH of the washing liquid is 7, wherein the volume ratio of the ammonia water added in step 2) to the ammonia water in step 1) is 0.6, and the volume ratio of the siloxane in step 2) to the tetraethyl orthosilicate in step 1) is 0.2;
[0042] 3) dispersing the prepared phenyl-modified silica-coated magnetic particles in ethanol to prepare a 5 g / mL ethanol dispersion of phenyl-modified silica-coated magnetic particles, adding graphene powder, stirring at 45° C. and 250 rpm for 10 h, and assembling the two together through the π-π stacking effect of the non-covalent bond between the phenyl groups in the phenyl-modified silica-coated magnetic particles and the graphene benzene rings, wherein the mass ratio of the graphene powder to the phenyl-modified silica-coated magnetic particles is 5;
[0043] 4) The magnetic graphene ethanol dispersion is dispersed in the paint and applied to the surface coating of the building. During construction, the prepared magnetic graphene paint is first sprayed on the surface of the object to be constructed, and then an energized conductive coil is used to scan the surface of the constructed coating. The magnetic field generated by the conductive coil causes the magnetic graphene to be stacked and oriented layer by layer to form a uniform coating.
[0044] 5) After the coating is completely dry, scrape off the formed graphene coating and perform a Raman spectrum test to test the intensity ratio of the D peak to the G peak.
[0045] In this embodiment, the intensity ratio of the D peak to the G peak is 0.55.
[0046] Embodiment 3:
[0047] 1) Preparation of silica-coated magnetic particles: Nano-iron oxide powder with a particle size of 100 nm and an ethanol aqueous solution were stirred and mixed at a speed of 2500 rpm for 20 min, tetraethyl orthosilicate was added at a drop rate of 15 mL / min and continued to stir for 45 min, and then ammonia water was added and continued to stir for 1 h, the volume ratio of ethanol to water in the ethanol aqueous solution was 10, the volume ratio of ethanol to tetraethyl orthosilicate was 10, and the volume ratio of ethanol to ammonia water was 2.5;
[0048] 2) continuing to add ammonia water, and then adding dimethyldiphenylsiloxane at 5 mL / min, continuing to stir at a speed of 1000 rpm for 2 hours, and then filtering and washing until the pH of the washing liquid is 7, wherein the volume ratio of the ammonia water added in step 2) to the ammonia water in step 1) is 0.8, and the volume ratio of the siloxane in step 2) to the tetraethyl orthosilicate in step 1) is 0.3;
[0049] 3) dispersing the prepared phenyl-modified silica-coated magnetic particles in ethanol to prepare a 10 g / mL ethanol dispersion of phenyl-modified silica-coated magnetic particles, adding graphene powder, stirring at 35° C. and 500 rpm for 20 h, and assembling the two together through the π-π stacking effect of the non-covalent bond between the phenyl groups in the phenyl-modified silica-coated magnetic particles and the graphene benzene rings, wherein the mass ratio of the graphene powder to the phenyl-modified silica-coated magnetic particles is 10;
[0050] 4) The magnetic graphene ethanol dispersion is dispersed in the paint and applied to the surface coating of the building. During construction, the prepared magnetic graphene paint is first sprayed on the surface of the object to be constructed, and then an energized conductive coil is used to scan the surface of the constructed coating. The magnetic field generated by the conductive coil causes the magnetic graphene to be stacked and oriented layer by layer to form a uniform coating.
[0051] 5) After the coating is completely dry, scrape off the formed graphene coating and perform a Raman spectrum test to test the intensity ratio of the D peak to the G peak.
[0052] In this embodiment, the intensity ratio of the D peak to the G peak is 0.49.
[0053] Comparative Example
[0054] 1) dispersing the original graphene in ethanol to prepare a 10 g / mL graphene dispersion, and stirring at 40° C. at a speed of 1000 rpm for 24 h;
[0055] 4) The graphene ethanol dispersion is dispersed in the paint and applied to the surface coating of the building. During construction, the prepared magnetic graphene paint is first sprayed on the surface of the object to be constructed, and then an energized conductive coil is used to scan the surface of the constructed coating. The magnetic field generated by the conductive coil causes the magnetic graphene to be stacked and oriented layer by layer to form a uniform coating.
[0056] 5) After the coating is completely dry, scrape off the formed graphene coating and perform a Raman spectrum test to test the intensity ratio of the D peak to the G peak.
[0057] In this embodiment, the intensity ratio of the D peak to the G peak is 1.12.
[0058] The ratio of the D peak to the G peak intensity of the Raman spectrum is one of the effective ways to reflect the order of graphene. The smaller the value, the better the order of graphene. By comparing Examples 1-3 with the comparative example, the magnetic graphene prepared by the present invention can be oriented in an electromagnetic field.
[0059] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing magnetic graphene that can be oriented in a magnetic field, characterized in that: The following steps are involved: 1) Preparation of silica-coated magnetic particles: magnetic nanoparticles are stirred and mixed with an aqueous solution of ethanol, and then tetraethyl orthosilicate is added and stirred continuously, and then ammonia water is added and stirred continuously; 2) Preparation of phenyl-modified silica-coated magnetic particles: first add ammonia water, then add siloxane and continue stirring, then filter and wash until the pH of the washing solution is 7; 3) Preparation of magnetic graphene: The prepared phenyl-modified silica-coated magnetic particles are dispersed in ethanol, and then graphene powder is added and stirred at a certain temperature, so that the two are assembled together through the π-π stacking effect of the non-covalent bond between the phenyl groups in the phenyl-modified silica-coated magnetic particles and the graphene benzene rings; 4) Orientation of magnetic graphene in a magnetic field: The magnetic graphene ethanol dispersion is applied to the surface coating of a building. During construction, the prepared magnetic graphene ethanol dispersion is first sprayed on the surface of the object to be constructed, and then an energized conductive coil is used to scan the surface of the coating to be constructed. The magnetic field generated by the conductive coil causes the magnetic graphene to be stacked and oriented layer by layer to form a uniform coating.
2. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: The magnetic nanoparticles in step 1) are nano iron powder, nano ferroferric oxide powder, nano nickel powder, nano steel powder, and have a particle size of 1-500 nm.
3. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: In the step 1), the volume ratio of ethanol to water in the ethanol aqueous solution is 2-10, the volume ratio of ethanol to tetraethyl orthosilicate is 5-20, and the volume ratio of ethanol to ammonia water is 1-2.
5.
4. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: In step 1), the dropping speed of tetraethyl orthosilicate is 0.5-20 mL / min.
5. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: In step 1), the stirring speed is 500-5000 rpm, the stirring time of the magnetic nanoparticles and the ethanol aqueous solution is 10-60 min, the stirring time after adding tetraethyl orthosilicate is 10-60 min, and the stirring time after adding ammonia water is 0.5-4 h.
6. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: The siloxane in step 2) is one or more of phenyl trimethyl siloxane, methyl phenyl siloxane, and dimethyl diphenyl siloxane.
7. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: The volume ratio of the ammonia water added in step 2) to the ammonia water in step 1) is 0.25-0.8, and the volume ratio of the siloxane in step 2) to the tetraethyl orthosilicate in step 1) is 0.05-0.
4.
8. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: The dropping speed of siloxane in step 2) is 0.1-15 mL / min, the stirring speed in step 2) is 500-5000 rpm, and the stirring time is 0.5-5 h.
9. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: In step 3), the concentration of the ethanol dispersion of the phenyl-modified silica-coated magnetic particles is 2-20 g / L, and the mass ratio of the graphene powder to the phenyl-modified silica-coated magnetic particles is 0.5-20.
10. The method for preparing magnetic graphene that can be oriented in a magnetic field according to claim 1, characterized in that: In step 3), the stirring rate is 100-500 rpm, the stirring temperature is 30-70° C., and the stirring time is 10-24 h.
Citation Information
Patent Citations
High-barrier composite material and preparation method based on two-dimensional nanofiller magnetic induced orientation
CN105733189A
Magnetic Fenton-like catalyst, and preparation method and application thereof
CN106362746A
Graphene oxide covalently bonded and coated magnetic nanoparticle composite material and preparation method thereof
CN106540658A
Aqueous anticorrosive coating and preparation method thereof
CN109294407A
High-performance transparent anticorrosive coating material and preparation method thereof
CN114773959A
Cited By
Graphene-based anti-permeation interface treating agent as well as preparation method and construction method thereof
CN121872798A
A graphene-based anti-permeation interface treatment agent and a preparation method and construction method thereof
CN121872798B